Transformasi Praktik Pembelajaran Guru Melalui Bimbingan Teknis Pembelajaran Deep Learning di Lingkungan Sekolah Muhammadiyah - Dedek Helida Pitra; Khairul Saleh (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2026)
The low level of Indonesian students’ critical thinking skills, as indicated by the results of the Programme for International Student Assessment (PISA), suggests that school learning practices remain procedural in nature and have not yet promoted meaningful learning. In response to this condition, the Merdeka Curriculum encourages the implementation of deep learning; however, its application is still constrained by teachers’ limited conceptual understanding and pedagogical skills. This community service program aimed to transform teachers’ instructional practices in Muhammadiyah schools in Bungo Regency through Technical Guidance on Deep Learning. The program employed a participatory action-based approach, actively involving teachers through stages of needs analysis, conceptual reinforcement, practical design of deep learning-based instruction, development of authentic assessment, and reflection and evaluation. The activities were conducted through face-to-face sessions combining material delivery, discussion, and direct mentoring. The results indicate an improvement in teachers’ understanding of deep learning concepts and principles, as well as their ability to translate them into instructional products, including deep learning-based lesson plans or teaching modules and more contextual assessment instruments oriented toward the development of critical thinking skills. Teachers began to integrate learning experiences of understanding, applying, and reflecting, and to utilize formative and authentic assessment as integral components of the learning process, thereby contributing to improved instructional quality in partner schools.